Direct democracy, political delegation, and responsibility substitution - Carlo Prato; Bruno Strulovici (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2010)
Can direct democracy provisions improve welfare over pure representative democracy? This paper studies how such provisions affect politicians' incentives and selection. While direct democracy allows citizens to correct politicians' mistakes, it also reduces the incentives of elected representatives to search for good policies. This responsibility substitution reduces citizens' ability to screen competent politicians, when elections are the only means to address political agency problems. A lower cost of direct democracy induces a negative spiral on politicians incentives, which we characterize by a disincentive multiplier. As a consequence, introducing initiatives or lowering their cost can reduce voters' expected utility. Moreover, when elections perform well in selecting politicians and provide incentives, this indirect welfare reducing effect is stronger.
Keywords: D72; D78; P16; 330; Direct Democracy; Initiative; Referendum; Political Agency; Delegation